2021
DOI: 10.1111/joor.13224
|View full text |Cite
|
Sign up to set email alerts
|

Changes in oral and cognitive functions among older Japanese dental outpatients: A 2‐year follow‐up study

Abstract: Background The relationship between oral and cognitive functions among older people is highly debated. Objective To examine whether oral functions are related to changes in the levels of mild cognitive impairment (MCI) biomarkers in older Japanese outpatients. Methods This observational study included 52 outpatients aged ≥65 years who underwent dental examinations at the Fukuoka Dental College Hospital. The Mini‐Mental State Examination (MMSE) was performed, and MCI blood biomarker levels were assessed at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Furthermore, the median MMSE score of MCI patients in this study was 24: lower than the cut-off MMSE score [ 41 ] for MCI diagnosis. This may be due to the participants in this study having been diagnosed with MCI based on a comprehensive evaluation using neuropsychological tests, such as the MMSE [ 24 ], in addition to neuroimaging and hematological tests and because many of them were patients who sought medical attention at a dementia clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the median MMSE score of MCI patients in this study was 24: lower than the cut-off MMSE score [ 41 ] for MCI diagnosis. This may be due to the participants in this study having been diagnosed with MCI based on a comprehensive evaluation using neuropsychological tests, such as the MMSE [ 24 ], in addition to neuroimaging and hematological tests and because many of them were patients who sought medical attention at a dementia clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that patients with MCI are more likely to have poor oral health and impairments in oral functions, such as oral diadochokinesis (ODK), which may be due to few remaining teeth and impaired tongue and lip motor function [ 21 23 ]. Furthermore, Mizutani et al [ 24 ] conducted a 2-year longitudinal study of older adults without dementia and reported that an increased risk of MCI, as assessed by MCI biomarkers, was associated with decreased masticatory ability. These findings suggest that oral health management by dental professionals is important for patients with MCI.…”
Section: Introductionmentioning
confidence: 99%
“…A penlight and dental tweezers were used for the examination, if they could confirm the tooth condition sufficiently. Teeth with residual roots not involved in occlusion and teeth with increased mobility (Miller’s classification 3) were excluded [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, they developed a measurement protocol before the initiation of the investigation, and measurements were conducted according to the procedure of the protocol. They examined and counted the number of teeth present in each participant, and teeth with increased mobility (Miller’s classification 3) and those without a crown were excluded from the count as they were nonfunctional [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The participants were instructed to chew the gum freely at a rate of once per second for 60 s at a comfortable point. The color of the chewed gum was measured on a 10-point scale immediately after chewing to minimize the color change with time [ 21 ].…”
Section: Methodsmentioning
confidence: 99%